2021
DOI: 10.24843/spektran.2021.v09.i02.p04
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Risiko Proyek Pembangunan Gedung Rsia Puri Bunda Tabanan - Bali

Abstract: The project implementation process from planning to implementation sometimes encounters problems ranging from cost, quality and time. In the implementation process, there are obstacles, namely the soil conditions in the image do not match the actual conditions and the architectural work undergoes a design change, because the previously planned floor plan does not match the desired function. These problems lead to the need for additional costs and additional time for project completion. This study aims to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research by Alaydrus & Hardjomuljadi (2018) found that ue to labor, material and design changes. Research by Perdana Putra et al (2021) found that causes of delay due to material problems, poor planning, management and supervision, while research by Putra (2022) fount it as obstacles to work caused rainfall, soil characteristics, access to inaccessible locations, and research, and research by Rofi Henindia & Suroso (2022), The cause of delay is due to auction problems, execution time problems, and execution method problems, while research by Rosdianto et al (2018) found he probability of delay obtained from the results of the FTA analysis is 0.7342, likewise the results of research by Darmawi et al (2020) main factors causing design changes, natural disasters, site conditions, while research by Darmawan & Yuwono, (2021) found the causes of delay are Covid 19 factors and resource readiness factors.…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…Research by Alaydrus & Hardjomuljadi (2018) found that ue to labor, material and design changes. Research by Perdana Putra et al (2021) found that causes of delay due to material problems, poor planning, management and supervision, while research by Putra (2022) fount it as obstacles to work caused rainfall, soil characteristics, access to inaccessible locations, and research, and research by Rofi Henindia & Suroso (2022), The cause of delay is due to auction problems, execution time problems, and execution method problems, while research by Rosdianto et al (2018) found he probability of delay obtained from the results of the FTA analysis is 0.7342, likewise the results of research by Darmawi et al (2020) main factors causing design changes, natural disasters, site conditions, while research by Darmawan & Yuwono, (2021) found the causes of delay are Covid 19 factors and resource readiness factors.…”
Section: Hypothesis Testingmentioning
confidence: 99%